A területfejlesztési képzés egyes jellemzői a hazai felsőoktatásban a 2010-es évek elején (Some Features of Education of Regional Policy in Hungarian Higher Education in the Early 2010s) - Pál Szabó; János Gyurkovics; Tamás Jancsó; Miklós Lukovics; János Schwertner (DETUROPE)
This paper is based on the lectures held at the conference of the Hungarian Society of Regional Science (2013, Kaposvár, Section: „The knowledge of EU regional policy in higher education”) on the one hand, and on the other hand it is based on studies and data of the education of regional policy experts. The aim of this paper is to give information about some current general and local specifics of the education of regional policy experts in Hungary.